PENINGKATAN PENGETAHUAN KESEHATAN REPRODUKSI PADA REMAJA DI SEKOLAH MENENGAH PERTAMA NEGERI 13 JAKARTA - Mulyati, Susi; Mahanani, Dian; Hutapea, Jhon Hendrik Sahat Marasi; Fakhirah, Annisa; Fatimah, Gefira Nur; Masruroh, Siti; Syakuli, Alifah Irdanti; Adriansyah, Moch; Fasa, Sabrina Putri (LPPM Universitas Flores, 2024)
Reproductive health is a state of complete physical, mental, and social well-being. It does not merely entail freedom from diseases related to the reproductive system, functions, and processes. Maintaining reproductive health is crucial for adolescents through adopting a healthy lifestyle and consuming vitamins. The age range for adolescents is typically between 10-20 years old, though according to the Indonesian Ministry of Health Regulation Number 25 of 2014, adolescents are defined as those aged 10 to 18 years. Adolescence begins with puberty, marked by physical and physiological changes. Reproductive health education should be introduced early, starting around 2,5-3 years old when children begin to be curious about their bodies. Parental education aims to help children understand reproductive health, emphasising the importance of personal hygiene, especially for adolescent girls. This education focuses on awareness and the importance of reproductive health and equipping children to make informed decisions in various situations. Community service initiatives aim to educate adolescents and improve their knowledge of reproductive health. An outreach activity was conducted on Friday, April 19, 2024, at SMPN 13 Jakarta, reaching 380 respondents directly through educational sessions. Evaluation involved pre-test and post-test questionnaires to measure knowledge levels, with results showing a significant increase in reproductive health knowledge among adolescents. Post-test results indicated high scores for 299 respondents (78.69%).